Efektivitas Model Pembelajaran Project Based Learning dengan Pendekatan Deep Learning terhadap Kemampuan Berpikir Reflektif pada Materi Rantai Makanan - Rezy Trifatimah; Rosmiati; Erlin Ladyawati (Paedagogie, 2026)
This study aims to determine the effectiveness of the Project Based Learning (PjBL) model with a Deep Learning approach on the reflective thinking ability of fifth-grade students on the topic of food chains. This research employed a quantitative approach using an experimental method with a pretest–posttest experimental design. The subjects of the study were fifth-grade students of SDN Kepuh Kiriman I Waru, consisting of two experimental classes, namely class V-B and class V-A, with 28 students in each class. The research instruments included reflective thinking essay tests in the form of pretest and posttest, observation sheets, student response questionnaires, and a reflective thinking attitude scale. Data were analyzed using descriptive analysis and the N-Gain test to determine the improvement in students’ reflective thinking abilities. The results showed that students' reflective thinking abilities improved, with an N-Gain score of 0.71 in experimental class 1 and 0.72 in experimental class 2, which are categorized as high. The average posttest scores also indicated good results, namely 84.44 in experimental class 1 and 85.93 in experimental class 2. In addition, questionnaire results showed that students responded positively to the learning process, and the reflective thinking attitude scale indicated a dominance of the “strongly agree” category across several indicators. Therefore, the Project Based Learning model with a Deep Learning approach is effective in improving students’ reflective thinking abilities on the topic of food chains.